Diagnosis of Taenia solium infections based on "mail order" RNA-sequencing of single tapeworm egg isolates from stool samples. - Henrik Sadlowski; Veronika Schmidt; Jonathan Hiss; Johannes A Kuehn; Christian G Schneider; Gideon Zulu; Alex Hachangu; Chummy S Sikasunge; Kabemba E Mwape; Andrea S Winkler; Markus Schuelke (PLoS Neglected Tropical Diseases)
Combined community health programs aiming at health education, preventive anti-parasitic chemotherapy, and vaccination of pigs have proven their potential to regionally reduce and even eliminate Taenia solium infections that are associated with a high risk of neurological disease through ingestion of T. solium eggs. Yet it remains challenging to target T. solium endemic regions precisely or to make exact diagnoses in individual patients. One major reason is that the widely available stool microscopy may identify Taenia ssp. eggs in stool samples as such, but fails to distinguish between invasive (T. solium) and less invasive Taenia (T. saginata, T. asiatica, and T. hydatigena) species. The identification of Taenia ssp. eggs in routine stool samples often prompts a time-consuming and frequently unsuccessful epidemiologic workup in remote villages far away from a diagnostic laboratory. Here we present "mail order" single egg RNA-sequencing, a new method allowing the identification of the exact Taenia ssp. based on a few eggs found in routine diagnostic stool samples. We provide first T. solium transcriptome data, which show extremely high mitochondrial DNA (mtDNA) transcript counts that can be used for subspecies classification. "Mail order" RNA-sequencing can be administered by health personnel equipped with basic laboratory tools such as a microscope, a Bunsen burner, and access to an international post office for shipment of samples to a next generation sequencing facility. Our suggested workflow combines traditional stool microscopy, RNA-extraction from single Taenia eggs with mitochondrial RNA-sequencing, followed by bioinformatic processing with a basic laptop computer. The workflow could help to better target preventive healthcare measures and improve diagnostic specificity in individual patients based on incidental findings of Taenia ssp. eggs in diagnostic laboratories with limited resources.